Giant basal cell carcinoma - Nasser,Nilton (2012)
The basal cell carcinoma is the most common skin cancer but the giant vegetating basal cell carcinoma reaches less than 0.5 % of all basal cell carcinoma types. The Giant BCC, defined as a lesion with more than 5 cm at its largest diameter, is a rare form of BCC and commonly occurs on the trunk. This patient, male, 42 years old presents a Giant Basal Cell Carcinoma which reaches 180 cm2 on the right shoulder and was negligent in looking for treatment. Surgical treatment was performed and no signs of dissemination or local recurrence have been detected after follow up of five years.